Evaluation of the Effects of Alpha Evaluation of the effects of Alpha Tocopherol, Quercetin and their combination on Ethanol-Induced pancreatic and duodenal mucosal injuries: An experimental study. (2024)
Aim: In this study, the effects of alpha-tocopherol (AT), quercetin (QT) or their combination on ethanol-induced pancreatic and duodenal mucosal damage were investigated in rats using morphological and biochemical evaluations. Study Design: Experimental study.Place and Duration of Study: University of Ibadan, Ibadan, Nigeria. Methodology: Ethanol-induced injuries were produced by oral administration of 40% ethanol (0.2 ml/day) for 40 consecutive days, while a control group of rats was served distilled water. Other groups received AT (2.5 mg/kg), QT (50 mg/kg) or their combination with 40% ethanol during the experimental period. Blood glucose level was significantly (p<0.05) increased in ethanol-treated rats relative to controls. Ethanol administration caused shrinkage of insulin-secreting islets tissues in the pancreas, while lesions such as erosions, loss of villi and severe inflammatory cell infiltrations of the mucosa and sub-mucosa were observed in the duodenum. These changes were accompanied by significant elevation in the levels of hydrogen peroxide (H2O2), malondialdehyde (MDA) and advanced oxidation protein products (AOPP) in the pancreas and duodenum, along with reduced activities of glutathione peroxidase (GPx) and glutathione S-transferase (GST). Treatment of rats with AT, QT, and especially their combination, yielded profound reversal of ethanol-induced effects indicated by restoration of blood glucose to control levels, preservation of pancreatic and duodenal morphology and the inhibition of ethanol-induced oxidative stress. Conclusion: Overall, dietary supplementation with AT and/or QT could potentially counteract the adverse effects associated with chronic alcohol consumption.